Assessment of the Subarachnoid Hemorrhage International Trialists (SAHIT) Models for Dichotomized Long-Term Functional Outcome Prediction After Aneurysmal Subarachnoid Hemorrhage in a United Kingdom Multicenter Cohort Study. Issue 6 (25th July 2020) - Hostettler, Isabel C; Pavlou, Menelaos; Ambler, Gareth; Alg, Varinder S; Bonner, Stephen; Walsh, Daniel C; Bulters, Diederik; Kitchen, Neil; Brown, Martin M; Grieve, Joan; Houlden, Henry; Werring, David J
Abstract: BACKGROUND: Long-term outcome after subarachnoid hemorrhage, beyond the first few months, is difficult to predict, but has critical relevance to patients, their families, and carers. OBJECTIVE: To assess the performance of the Subarachnoid Hemorrhage International Trialists (SAHIT) prediction models, which were initially designed to predict short-term (90 d) outcome, as predictors of long-term (2 yr) functional outcome after aneurysmal subarachnoid hemorrhage (aSAH). METHODS: We included 1545 patients with angiographically-proven aSAH from the Genetic and Observational Subarachnoid Haemorrhage (GOSH) study recruited at 22 hospitals between 2011 and 2014. We collected data on age, WNFS grade on admission, history of hypertension, Fisher grade, aneurysm size and location, as well as treatment modality. Functional outcome was measured by the Glasgow Outcome Scale (GOS) with GOS 1 to 3 corresponding to unfavorable and 4 to 5 to favorable functional outcome, according to the SAHIT models. The SAHIT models were assessed for long-term outcome prediction by estimating measures of calibration (calibration slope) and discrimination (area under the receiver-operating characteristic curve [AUC]) in relation to poor clinical outcome. RESULTS: Follow-up was standardized to 2 yr using imputation methods. All 3 SAHIT models demonstrated acceptable predictive performance for long-term functional outcome. The estimated AUC was 0.71 (95% CI: 0.65-0.76), 0.73 (95% CI: 0.68-0.77), and 0.74 (95% CI: 0.69-0.79) for the core, neuroimaging, and full models, respectively; the calibration slopes were 0.86, 0.84, and 0.89, indicating good calibration. CONCLUSION: The SAHIT prediction models, incorporating simple factors available on hospital admission, show good predictive performance for long-term functional outcome after aSAH. Graphical Abstract: